2013
DOI: 10.3389/fnins.2013.00167
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of ghrelin signaling in the PVN increases high-fat diet intake and body weight in stressed and non-stressed C57BL6J male mice

Abstract: Chronic social stress has been associated with increased caloric intake and adiposity. These effects have been linked to stress induced changes in the secretion of ghrelin, a hormone that targets a number of brain regions to increase food intake and energy expenditure and promote increased body fat content. One of the brain sites targeted by ghrelin is the hypothalamic paraventricular nucleus (PVN), a region critical for both the regulation of the stress response and the regulation of energy balance. Given the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Ghrelin, a hormone produced in the peripheral organs and central nervous system, is known to be involved in the regulation of appetite, gastrointestinal motility, and growth hormone release. Recently, the abnormal kinetics of ghrelin due to stress loading have been reported [ 1 3 , 9 , 10 ]. Intracerebroventricular administration of CRF or exposure to psychological stress suppresses food intake in association with decreases in peripheral ghrelin levels during fasting [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin, a hormone produced in the peripheral organs and central nervous system, is known to be involved in the regulation of appetite, gastrointestinal motility, and growth hormone release. Recently, the abnormal kinetics of ghrelin due to stress loading have been reported [ 1 3 , 9 , 10 ]. Intracerebroventricular administration of CRF or exposure to psychological stress suppresses food intake in association with decreases in peripheral ghrelin levels during fasting [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrated that whereas ghrelin receptor antagonist tended to inhibit food intake during the first two hours after injection ( Figure 5.3A and B), it obviously increased cumulative food intake in MKR mice and tended to increase it in FVB mice through long-term treatment ( Figure 5.4A and B). In consistent with that, a recent study showed that [D-Lys3]-GHRP-6 did not decrease stress-induced caloric intake, but paradoxically increased the intake of HFD (343). Moreover, the infusion of [D-Lys3]-GHRP-6 in a rat model did not have a significant impact on food intake and appetite (342).…”
Section: Discussionsupporting
confidence: 71%
“…The effects of ghrelin on the PVN under chronic stress conditions are also complex. Blocking GHSR in the PVN during chronic social defeat enhances the intake of a high calorie diet in stressed mice . One possible explaination for these data is that ghrelin acts on the PVN to enhance inhibitory tone onto CRH neurones as part of a negative‐feedback loop that tones down the HPA axis, and not producing ghrelin leaves CRH neurones at a lower threshold of activation.…”
Section: Ghrelin and The Hypothalamus In The Face Of Stressmentioning
confidence: 98%